Predictors of Long-Term Survival after Cardiopulmonary Resuscitation - Parivash Nazarpour; Fateme Jafaraghaee; Mohammad Taghi Moghadamnia; Saman Maroufizadeh (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Survival after cardiac arrest is one of the most important issues related to the safety and quality of patient care, and unexpected events such as failure to follow guidelines can endanger the patient's safety. Objective: This study aimed to determine the long-term survival after cardiopulmonary resuscitation and its predictors in patients with cardiac arrest. Materials and Methods: In this retrospective study, individual, disease-related, and 3-day follow-up-related factors were monitored after the cardiopulmonary resuscitation (CPR) in all patients with long-term survival after cardiac arrest (CA) who were discharged from the hospital between 2016 and 2019. Patients' survival or death after CPR was followed up by telephone interviews. The patient's survival time after discharge was calculated until the interview day. The obtained data were analyzed by the Kaplan-Meier and Cox regression tests. Results: Out of 1565 CPR cases (both In-Hospital Cardiac Arrest [IHCA] and Out-of-Hospital Cardiac Arrest [OHCA]), 667 were successful, of which 156 patients had long-term survival. The mean ±SD of the survival time for patients was 30.98 ±1.78 months. Significant variables in associations with long-term survival were old age (>60 y) (HR=1.811, 95%CI;1.019-3.218, P=0.043), initial asystole rhythm (HR=4.199; 95%CI:2.129-8.282; P=0.001), ventricular tachycardia (VT) (HR=2.315; 95%CI:1.171-4.576; P=0.016), connection to mechanical ventilator (HR=1.992; 95%CI:1.229-3.229; P=0.005), cardiovascular disease (HR=1.795; 95%CI:1.111-2.901; P=0.017), and abnormal SpO2 (HR=2.447; 95%CI:1.507-3.972; P=0.001). Multivariate analysis also showed that asystole rhythm (P=0.001), VT (P=0.052), and prolonged duration of CPR (>20 min) (P=0.043) significantly increase the risk of death. Conclusions: The major predictors in this study were age, initial rhythm, connection to a mechanical ventilator, CPR duration, cardiovascular disease, and SpO2 monitoring. Therefore, introducing post-resuscitation care protocols and conducting training programs and further studies are warranted.